Phonetic similarities and differences between japanese-chinese - Токкaринa A. М.; Aнипинa A. К. (Journal of Oriental Studies, 2017)
Characters in this article addresses phonetic similarities and differences between japanese-chinese characters. The aim of the study is examining the Japanese-Chinese characters, select phonetic and lexical difference. The study found that using adding determintiv prefixes to the fonoideografiče hieroglyph, you can get a new character.